Determinants of catastrophic health expenditure and impoverishment in low- and middle-income countries: A narrative review - Siri Hurul Aini (Privietlab, 2026)
Financial protection—ensuring that people can use the health services they need without suffering financial hardship—is a defining pillar of Universal Health Coverage (UHC) and is monitored globally through Sustainable Development Goal (SDG) indicator 3.8.2. In Low- and Middle-Income Countries (LMICs), where Out-of-Pocket (OOP) payments finance a large share of health spending, Catastrophic Health Expenditure (CHE) and medical impoverishment remain widespread and worsening on several metrics. This narrative review synthesizes the conceptual, methodological, and empirical literature on the determinants of CHE and impoverishment in LMICs. Drawing on seminal methodological contributions and country and multi-country studies published mainly between 2003 and 2025 and identified through structured searches of Scopus, Web of Science, and PubMed, the review maps competing definitions and thresholds (the budget-share 10%/25% SDG indicators and the World Health Organization’s 40% capacity-to-pay threshold), measurement debates, and the pathways that link illness to financial hardship. Determinants were organized thematically into household-level factors (economic status, chronic and non-communicable disease, hospitalization, ageing, and household composition), health-system factors (OOP financing share, absence of prepayment and pooling, provider payment, and medicine costs), and contextual factors (rural residence and regional inequality). Evidence on prepayment, insurance expansion, benefit design, exemptions, and essential medicines policy is appraised alongside its heterogeneity. The review concludes by identifying methodological limitations and a research agenda emphasizing longitudinal designs, distress financing, and the measurement of forgone care.